2018
DOI: 10.4149/bll_2018_017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leucine on NF-κB pathway in liver regeneration after partial hepatectomy in rats, as determined by miniarray analysis

Abstract: Our results suggested that valine, glutamine, and leucine amino acids may alter expressions of the genes of NF-κB signal pathway. In addition, among these amino acids, glutamine and valine proved to be much more effective on NF-κB signal pathway after the PH (Tab. 1, Ref. 41).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The geraniol (2,6-dimethyltrans-2,6-octadiene-8-ol or 3,7-dimethylocta-trans-2,6-diene-1-ol) used in our experimental study, is a monoterpene alcohol found in rose, lavender and lemon as well (Crespo et al, 2017). Geraniol is known to have antioxidant, anti-inflammatory, antimicrobial (Bhattamisra et al, 2019), antitumor (Cho et al, 2016), hepatoprotective (Mohammed, Tadros, Michel, 2020), cardioprotective, neuroprotective (Rekha, Sivakamasundari, 2018), antidiabetic (Babakumar et al, 2017) regenerative effects (Ceyhan, Canbek, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…The geraniol (2,6-dimethyltrans-2,6-octadiene-8-ol or 3,7-dimethylocta-trans-2,6-diene-1-ol) used in our experimental study, is a monoterpene alcohol found in rose, lavender and lemon as well (Crespo et al, 2017). Geraniol is known to have antioxidant, anti-inflammatory, antimicrobial (Bhattamisra et al, 2019), antitumor (Cho et al, 2016), hepatoprotective (Mohammed, Tadros, Michel, 2020), cardioprotective, neuroprotective (Rekha, Sivakamasundari, 2018), antidiabetic (Babakumar et al, 2017) regenerative effects (Ceyhan, Canbek, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Their aromatic properties are mainly attributable to the volatility of geraniol. In recent years, many researchers have centered on the active function of geraniol in the body, that is, its antibacterial [191] and anti-inflammatory [192] functions, improvement of oxidation resistance [192], potential to treat Parkinson's disease [193], promotion of liver regeneration [194], and potential anti-tumor properties [195]. Geranyl is a group derived from vanillin by the removal of hydroxyl, with geranyl pyrophosphate (GPP) and geranyl pyrophosphate (GGPP) among the leading derivatives of geranyl.…”
Section: Geraniolmentioning
confidence: 99%